Online flames how social identity in virtual communities influences political flaming behavior of young adult Facebook users - Morada, Ma. Caselyn B.; Paragas, Fernando dlC (Quezon City College of Mass Communication, University of the Philippines, 2023)
This study sought to delve into the relationship between social identity and political flaming, a form of reactive aggression, of young adult Facebook users in their virtual communities. Framed by Walther's Computer-Mediated Communication (CMC) model, the research further utilized the Social Identity model of Deindividuation Effects (SIDE) as its theoretical foundation. The study garnered insights from an online survey accomplished by 402 respondents. The results showed that both cognitive and strategic anonymity, although weak, are positively correlated with group norms. A weak yet positive correlation was discovered between group attraction and both types of flaming behaviors, while a strong positive correlation was identified between group norms and flaming behaviors, emphasizing the role of group norms in shaping individual behaviors. Cognitive anonymity was found to be positively but weakly correlated to flaming behaviors. Further, verbal aggression was found not to moderate the relationship between social identity variables and flaming behaviors, but political variables exhibited a moderating influence on the impact of group attraction on flaming behaviors.

Keywords: anonymity, social identity, group attraction, group norms, political flaming, flaming acceptability, flaming intention, verbal aggression, political knowledge, political participation
Vita.
Thesis
Includes bibliographical references (pages 199-218) and appendices (pages 219-236).
Keywords: Social identity -- Philippines; Online social networks -- Philippines; Aggressiveness